Design and In Vitro Evaluation of Chrono Modulated Theophylline Tablets - Kumar, B Vijaya; Nagaraj, B; Agaiah, B; Rambhau, D (Stamford Journal of Pharmaceutical Sciences, 2009)
The objective of this research work was to prepare a chrono modulated delivery system to meet chronopharmacological needs of asthma. In this study theophylline was selected as a model drug. To meet this objective we considered an initial lag phase of release for 3-5 hrs and later a rapid (surge) release phase. To achieve surge release a rapidly releasing core tablet of theophylline was developed by admixing theophylline with effervescent granules and super disintegrants. The lag phase in release was achieved by coating the EV core tablets with release retarding polymer EUDRAGIT RS-100 containing HPMC, further over coated with enteric polymer CAP. The results indicate that a rapidly releasing EV tablet of theophylline cab be developed which when coated with the polymers a lag phase of 2 hrs was achievable followed by a surge release. Key Words: Theophylline, Chrono Modulated Drug Delivery, Asthma. doi:10.3329/sjps.v1i1.1782 S. J. Pharm. Sci. 1(1&2): 25-28